Analyzing the use of quick response (QR) payment: Impulsive purchase as a behavioral finance effect - Budi Rustandi Kartawinata; Aldi Akbar (Journal of Innovation in Business and Economics, 2025)
This study examines the widespread use of quick response (QR) or barcode payments in Indonesian society, focusing on their impact on impulsive buying behavior. As mobile payment methods become increasingly prevalent, understanding their influence on consumer behavior—particularly impulsive purchasing—has become increasingly important. This research employs a quantitative approach, incorporating surveys and consumer interviews. The findings indicate that consumers who use QR payments are more likely to engage in impulsive spending. Additionally, the availability of QR payment options is identified as a significant factor influencing impulsive buying behavior. Furthermore, the accessibility features of QR payment systems are found to have a substantial impact on impulsive purchase decisions.